2018
DOI: 10.1016/j.envint.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the exposure of humans and the environment to oil pollution in the Niger Delta using advanced geostatistical techniques

Abstract: The Niger Delta is one of the largest oil producing regions of the world. Large numbers and volumes of oil spills have been reported in this region. What has not been quantified is the putative exposure of humans and/or the environment to this hydrocarbon pollution. In this novel study, advanced geostatistical techniques were applied to an extensive database of oil spill incidents from 2007 to 2015. The aims were to (i) identify and analyse spill hotspots along the oil pipeline network and (ii) estimate the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 33 publications
(48 reference statements)
1
47
0
Order By: Relevance
“…The results obtained in this study indicated that the environment has been polluted and the total petroleum hydrocarbon concentrations in water sample at the wellhead stations were above 10 mg l -1 which is the maximum permissible limit recommended by the Federal Ministry of Environment in Nigeria [110]. In a related study, Obida et al [42] used spatio-temporal analysis techniques to identify petroleum hydrocarbon pollution hotspots along the pipeline network, and to quantify the exposure of residents and the environment to petroleum hydrocarbons pollution in the Niger Delta region. The results obtained in this study demonstrate the high levels of environmental and human exposure to petroleum hydrocarbon pollutants in the Niger Delta [42].…”
Section: Human Health Implications Of Petroleum Hydrocarbon Contaminamentioning
confidence: 64%
See 4 more Smart Citations
“…The results obtained in this study indicated that the environment has been polluted and the total petroleum hydrocarbon concentrations in water sample at the wellhead stations were above 10 mg l -1 which is the maximum permissible limit recommended by the Federal Ministry of Environment in Nigeria [110]. In a related study, Obida et al [42] used spatio-temporal analysis techniques to identify petroleum hydrocarbon pollution hotspots along the pipeline network, and to quantify the exposure of residents and the environment to petroleum hydrocarbons pollution in the Niger Delta region. The results obtained in this study demonstrate the high levels of environmental and human exposure to petroleum hydrocarbon pollutants in the Niger Delta [42].…”
Section: Human Health Implications Of Petroleum Hydrocarbon Contaminamentioning
confidence: 64%
“…This accounts for more than 70 % of the overall hydrocarbon reserves of sub-Saharan Africa [34,37]. Although the Niger Delta region is one of the most petroleum hydrocarbons resource-rich regions in the world, it remains mired in cycles of conflicts that have perpetuated underdevelopment, threaten human security [21,39], habitat destruction [40], bunkering/artisanal refining and petroleum contamination of the natural environment [1,5,17,31,41,42]. Overall, a brief history of petroleum exploration and production in the Niger Delta region has been extensively reviewed by few researchers [1,5,43].…”
Section: The Niger Delta Region Of Nigeria and Petroleum Hydrocarbonsmentioning
confidence: 99%
See 3 more Smart Citations